Analysis of factors towards the development of a supply chain resiliency assessment tool - Junsay, Kimberly D (Animo Repository, 2022)
Given the recent events that have occurred in today’s day and age, disruptions in the supply chain are more frequently occurring and it is most likely that resilient supply chains are the ones that could push forward and get its operations back to normal despite experiencing disruptions. Therefore this paper presents a study in developing a supply chain resiliency assessment tool that is aimed to aid MSME enterprises in assessing their own business. Review of previous studies related to supply chain resiliency were analyzed in order to determine the dimensions affecting supply chain resiliency of a MSME; from which it has initially been determined that there are a total of 14 dimensions affecting it and factors affecting each dimension have also been distinguished. The study uses a variation of validation methods such as: (1) Lawshe’s Method on Content Validity Ratio where experts were consulted; (2) Cronbach’s Alpha for the reliability of the questionnaire from the answers of the respondents; and (3) Structural Equation Modeling to provide a graphical representation of the factor analysis, the groups are connected between each other to represent the correlation coefficient, and each group is connected to the dependent variable to also represent the correlation coefficient of each group and itself. With that, from the initially 14 dimensions determined that affects the supply chain resiliency of a MSME it has been narrowed down to only 4 which are the following: flexibility, integration, market strength, and criticality. These four key dimensions were analyzed and subsequently assessed their relative strengths and weaknesses within a given supply chain. The findings revealed that, while these dimensions are important, there are other factors that also contribute to the overall effectiveness of a supply chain. For instance, it was found that communication and collaboration among supply chain partners play a significant role in achieving optimal performance. Additionally, the study was able to accomplish the development of a tool that can be used to identify the strengths and weaknesses of a supply chain using Excel Visual Basic that can be used to identify the strengths and weaknesses of a supply chain and make recommendations for improvement. Overall, the research highlights the importance of taking a holistic approach to supply chain management and considering various factors beyond just the four dimensions that were highlighted by this study.